Variability in effective moisture inferred from inclusion fluid δ18O and δ2H values in a central Sierra Nevada stalagmite (CA). (1st March 2022) - Wortham, Barbara E.; Montañez, Isabel P.; Swart, Peter K.; Vonhof, Hubert; Tabor, Clay
Abstract: The oxygen isotopic composition of stalagmites is widely used to infer regional changes in terrestrial surface temperatures and precipitation dynamics. The stalagmite δ 18 O values, however, record the influence of multiple environmental conditions (e.g., temperature, precipitation source and amount) as well as in-cave physicochemical processes and possible disequilibrium precipitation effects. The δ 18 O and δ 2 H values of fluids entombed in stalagmites as inclusions have the potential to be robust proxies of paleo-precipitation δ 18 O and δ 2 H. Here we analyze the inclusion-fluid δ 18 O and δ 2 H values for a stalagmite from a central Sierra Nevada foothill cave, McLean's Cave, to reconstruct changes in effective moisture (precipitation – evaporation) in the region over the last deglaciation (20–13 ka). The results demonstrate high variability in inclusion-fluid δ 18 O and δ 2 H values and further suggest that the δ 18 O and δ 2 H values have several intervals driven by disequilibrium dis oxygen isotopic fractionation. These findings demonstrate that effective moisture was likely lower during past warm periods in comparison to some colder periods, consistent with other stalagmite calcite-based paleoclimate records from the southwestern United States. Highlights: A refined methodology with cavity ring down spectrometry is used to measure the O and H isotopic values of inclusion-fluids. This methodology allowed for the first inclusion-fluid stable isotope results from the western United States. Fluid stable isotope results from a central Sierra Nevada cave reveal variable effective moisture over the last deglaciation.